Does the modified Glasgow Prognostic Score aid in the management of patients undergoing surgery for a soft-tissue sarcoma?: an international multicentre study. (1st January 2022) - ,; Spence, Stephanie; Doonan, James; Farhan-Alanie, Omer M.; Chan, Corey D.; Tong, Daniel; Cho, Hwan Seong; Sahu, Muhammad A.; Traub, Frank; Gupta, Sanjay
Abstract : Aims: The modified Glasgow Prognostic Score (mGPS) uses preoperative CRP and albumin to calculate a score from 0 to 2 (2 being associated with poor outcomes). mGPS is validated in multiple carcinomas. To date, its use in soft-tissue sarcoma (STS) is limited, with only small cohorts reporting that increased mGPS scores correlates with decreased survival in STS patients. Methods: This retrospective multicentre cohort study identified 493 STS patients using clinical databases from six collaborating hospitals in three countries. Centres performed a retrospective data collection for patient demographics, preoperative blood results (CRP and albumin levels and neutrophil, leucocyte, and platelets counts), and oncological outcomes (disease-free survival, local, or metastatic recurrence) with a minimum of two years' follow-up. Results: We found that increased mGPS, tumour size, grade, neutrophil/lymphocyte ratio, and disease recurrence were associated with reduced survival. Importantly, mGPS was the best at stratifying prognosis and could be used in conjunction with tumour grade to sub-stratify patient survival. Conclusion: This study demonstrated that prognosis of localized STS strongly correlates with mGPS, as an increasing score is associated with a poorer outcome. We note that 203 patients (41%) with an STS have evidence of systemic inflammation. We recommend the mGPS and other biochemical blood indicators be introduced into the routine diagnostic assessment in STS patients to stratify patient prognosis. Its use will support clinical decision-making, especially when morbid treatment options such as amputation are being considered. Cite this article: Bone Joint J 2022;104-B(1):168–176.